Loss of function of OsMADS3 via the insertion of a novel retrotransposon leads to recessive male sterility in rice (Oryza sativa). (September 2015) - Zhang, Li; Mao, Donghai; Xing, Feng; Bai, Xufeng; Zhao, Hu; Yao, Wen; Li, Guangwei; Xie, Weibo; Xing, Yongzhong
Highlights: A spontaneous mutant R127S exhibiting recessive male sterile. Loss of function of OsMADS3 resulted in the recessive sterility of R127S. A retrotransposon insertion destroyed the function of OsMADS3 . OsMADS3 is very conserved across cultivars and wild rice. R127S is a good mediator for current selection due to its wide compatibility. Abstract: Natural mutation is the source of natural variation, which is the fundamental basis for the genetic improvement of crops. During the process of developing a recombinant inbred line (RI), a spontaneous mutagenesis in RI127 led to the production of the recessive male-sterile line RI127S. Via a map-based cloning approach, the gene controlling the male sterility was identified as OsMADS3, which was previously reported to be associated with floral organ development and male sterility. Thermal asymmetric interlaced PCR isolated one 1633-bp insertion in OsMADS3 in RI127S, which damaged its function due to failed transcription. The 1633-bp insertion was derived from a fragment flanked by retrotransposon genes on chromosome 5. Seven haplotypes of OsMADS3 were observed among 529 cultivars and 107 wild rice accessions, and 98% of the investigated genotypes carried the same H2 haplotype, indicating that OsMADS3 is highly conserved. RI127S has the combined genome constitution of its parents, indica rice Teqing and japonica 02428, and carries the widely compatible S5 gene donated by 02428. RI127 exhibits good performance in regard to its agronomic traits and has a wide compatibility. Therefore, RI127S would be an elite mediator for recurrent breeding in cases requiring a tedious hand-crossing-based inter-crossing phase. RI127S can be crossed not only with indica rice but also with japonica rice, thus providing breeders with flexible arrangements in recurrent breeding programs.